Enhancing algal growth and nutrient recovery from anaerobic digestion piggery effluent by an integrated pretreatment strategy of ammonia stripping and flocculation - Qian, Jun; Xu, Chengyu; Song, Hanwu; Zhou, Wenguang; Toda, Tatsuki; Li, Hongwu; Takayama, Yoshiki; Sekine, Mutsumi; Koga, Shinichi; Li, Jun; Liu, Jin (Frontiers in Bioengineering and Biotechnology, 2023)
Anaerobic digestion piggery effluent (ADPE) with a quite high ammonium (NH4+) concentration and turbidity (dark brown color) generally requires high dilution before microalgae cultivation, owing to its NH4+ toxicity and color inhibition to algal growth. An integrated pretreatment strategy of ammonia stripping and chemical flocculation may be a more practical pretreatment procedure for enhancing algae yield and nutrient recovery from anaerobic digestion piggery effluent. In this study, we determined the optimum pretreatment strategy of anaerobic digestion piggery effluent for subsequent microalgae cultivation and nutrient recovery. The results showed that the integrated anaerobic digestion piggery effluent pretreatment strategy of high-temperature ammonia stripping and chemical flocculation at a mixed dosage of 2 g L−1 polyaluminum chloride (PAC) and 40 mg L−1 cationic polyacrylamide (C-PAM), and 50 mg L−1 ammonium nitrogen (NH4+-N) enrichment provided maximum algal yield (optical density = 1.8) and nutrient removal (95.2%, 98.7%, 99.3%, and 78.5% for the removal efficiencies of total nitrogen, NH4+-N, total phosphorus, and chemical oxygen demand, respectively) from anaerobic digestion piggery effluent. The integrated pretreatment strategy is expected to become a more practical pretreatment procedure for enhancing algae yield and nutrient recovery from anaerobic digestion piggery effluent.